2015
DOI: 10.1007/s10562-015-1577-5
|View full text |Cite
|
Sign up to set email alerts
|

The Promoting Effect of Fe Doping on Rh/CeO2 for the Ethanol Synthesis

Abstract: The effects of Fe promotion were investigated on the activity and selectivity of Rh/CeO 2 catalyst for the direct synthesis of ethanol from syngas. The catalysts were comprehensively characterized by X-ray diffraction (XRD), N 2 adsorption-desorption, CO uptake, H 2 -TPR, temperature programmed surface reaction (TPSR), and FT-IR. XRD, CO uptake and FT-IR measurements indicated that Rh particles were well dispersed. TPSR results revealed that the addition of Fe changed CO dissociation behavior over the catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Cobalt in the catalyst surface is more favorable for hydrogenation; therefore, as shown in Figure d, with decreasing cobalt content, the CO dissociation decreases. As higher alcohol selectivity is achieved by a moderate hydrogenation ability, better alcohol selectivity is observed with the caesium‐modified 5Co–15Cu catalyst. The addition of caesium enhances the amount of chemisorbed CO on the surface of the catalyst and hence, the ability of CO dissociation increases in the presence of caesium.…”
Section: Resultsmentioning
confidence: 97%
“…Cobalt in the catalyst surface is more favorable for hydrogenation; therefore, as shown in Figure d, with decreasing cobalt content, the CO dissociation decreases. As higher alcohol selectivity is achieved by a moderate hydrogenation ability, better alcohol selectivity is observed with the caesium‐modified 5Co–15Cu catalyst. The addition of caesium enhances the amount of chemisorbed CO on the surface of the catalyst and hence, the ability of CO dissociation increases in the presence of caesium.…”
Section: Resultsmentioning
confidence: 97%
“…Previous work suggests that Rh-Fe 3+ -O species are active sites for the generation of C 2 oxygenates such as ethanol [5,9]. Considering the contribution of Rh 0 and Rh + to CO insertion ability, the active site for ethanol formation over Rh-Fe/ Al 2 O 3 catalyst was assumed to the (Rh x 0− Rh y + ) -O-Fe 3+ (Fe 2+ ) sites with reference to that of Rh-Mn catalysts [18]. These active sites could be formed by the close contact between Rh and Fe.…”
Section: Catalytic Performance Of Catalystsmentioning
confidence: 99%
“…Mo et al [17] found Fe decreased CO adsorption but improved hydrogenation ability of Rh-based catalysts. Liu et al [18] found that the doping of Fe changed CO dissociation behavior over Rh/CeO 2 catalyst during the experiments of CO adsorption and CO temperature programmed surface reaction (TPSR). Therefore, DRIFTS technique would be a very useful tool to understand the promotion of promoter from the view of elementary steps of ethanol formation, and to explain the difference in catalytic activity from a different view.…”
Section: Introductionmentioning
confidence: 99%
“…Much less work was conducted for CO adsorption on Rh/CeO 2 at a low temperature because the bulk of the work, mostly by IR, was conducted for the purpose of water gas shift reaction (WGSR), syngas conversion, ethanol synthesis from syn gas, and CO oxidation among other reactions [17][18][19][20]. The Rh/CeO 2 catalysts themselves have been well studied for decades where metallic Rh particles are formed upon reduction, although the as prepared Rh/CeO 2 contains Rh particles with several oxidation states and possibilities of Rh ions substitution of Ce cations [21,22].…”
Section: Introductionmentioning
confidence: 99%